Integrated spatial cost-benefit analysis of large-scale mangrove conservation and restoration in Indonesia - van Zanten, Boris; Brander, Luke McKinnon; Castaneda, Juan-Pablo; Herrera, Diego; Kaczan, David; Brown, Benjamin M.; Smith, Ian Andrew; Jongman, Brenden (Frontiers in Environmental Science, 2025)
Economic development in Indonesia has resulted in reduced poverty but has also been accompanied by significant pressure on natural capital, including its mangrove forests. In recognition of the role of mangroves in providing coastal protection and the delivery of other ecosystem services, the Government of Indonesia has engaged in several policy actions, among others the use of nature based solutions and has set a target to restore or enhance the protection of 600,000 ha of mangroves by 2025. The objective of the analysis presented in this paper is to inform the design and development of a national-scale mangrove conservation and restoration policy for Indonesia through a spatially explicit cost-benefit analysis. The analytical framework involves the integration of maps, data and models to estimate the costs and benefits of mangrove restoration at a high spatial resolution. On the benefit side, we make use of meta-analytic value transfer methods to value changes in fisheries, raw materials, coastal protection, carbon sequestration and avoided emissions, and mangrove tourism. On the cost side, we assess the opportunity and implementation costs using country specific data. Through a spatial overlay of cost and benefit estimates, cost-benefit indicators are calculated per district for investing in additional mangrove restoration and conservation. Using a discount rate of 5.5% and a 30-year project lifetime, the benefit-cost ratios of mangrove conservation and restoration are found to be >1 in most districts indicating positive social returns on investment. We find that mangrove conservation generally has higher benefit-cost ratios than restoration due to both the higher cost of restoration implementation and the additional time that it takes for restored mangroves to deliver ecosystem services. The spatially explicit framework to estimate district-level costs and benefits reveals tradeoffs with agriculture and aquaculture and enables the evaluation of investment scenarios and the spatial prioritisation of investments in mangrove conservation and restoration across Indonesia. Strategic allocation of conservation and restoration investments across districts can potentially significantly increase the economic viability of this nature-based solution.